OPTIMIZATION OF PHOTOGRAPHY SERVICES ORDERING SYSTEM - Pulla Pandika Widodo; Fitri Pratiwi; Al Malikul Ikhwanda Putra (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
The data management system that is currently running at Casamia Studio still uses a handwritten manual system which is prone to various errors that cause calculation errors, difficulty in determining prices, difficulties in searching data, and difficulties in obtaining the required reports. The purpose of this research is to be able to design a web-based information system that is easy to use. In this writing the author designed an information system at Casamia Studio that makes it easier for users to manage various existing service data. The author also uses the Waterfall method to meet the needs of this research. The new system results in an online ordering process, good and correct data storage, and can generate reports quickly and accurately. The existence of this information system is able to help green photography activities more effectively and efficiently in data processing.